ANALISIS KONFLIK SOSIAL DALAM NOVEL RENCANA BESAR UNTUK MATI DENGAN TENANG KARYA WISNU SURYANING ADJI - Arya Prapanca, Octavino; Irawan, Dody; Dwi Leoni, Tessa; Mustado, Maulida; Habiba, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of social conflict contained in the novel "Rencana Besar untuk Mati dengan Tenang" by Wisnu Suryaning Adji. The method used in this study is content analysis. The instrument in this study is the researcher himself, as the first instrument and supported by research tools. The data in this study are quotes contained in the novel "Rencana Besar untuk Mati dengan Tenang" by Wisnu Suryaning Adji. The data collection technique used to obtain research data is the documentation technique or library study, while the data validity technique uses the source triangulation technique. The results of the study show that there are 2 forms of social conflict, namely (1) conflict between organized and unorganized groups which is an ideological conflict between members of official and unofficial groups, (2) conflict between national units which is the people's disappointment with officials, policies, and government decisions. Based on the results of data analysis, there are 6 data from the 2 forms of social conflict, the following is the description: 1) there are 3 data on the conflict between organized and unorganized groups, and 2) there are 3 data on the conflict between national units.